ADVANCING CONSUMER PROTECTION THROUGH PRODUCT LIABILITY UNDER THE CONSUMER PROTECTION ACT 1999 - CHEE HUI BING; SIVANESVARAN CHOKKALAN; SUMATHI MUTHUKRISHNAN (International Conference On Law And Social Sciences, 2024)
This article explores critical aspects of tort law as a mechanism for consumer protection, with a focused analysis on product liability as delineated in Part X, Product Liability of Malaysia's Consumer Protection Act 1999. It scrutinizes the interplay of tort law with statutory laws to safeguard consumers from the risks associated with defective products. Through an examination of the Consumer Protection Act 1999, this study highlights how the Act's provisions on product liability integrate with traditional tort principles to enhance consumer safety and ensure manufacturers' accountability. The article provides key definitions such as “consumer”,“producer,” “product,” and “damage” and investigates the criteria for establishing liability and the remedies available to consumers. By assessing the effectiveness of these legal frameworks in promoting product safety and fairness in the marketplace, the article identifies the synergies between the Act and tort law, offering insights into their collective impact on consumer protection in Malaysia. This article aims to provide some insights into the role played by tort law in consumer protection, suggesting areas for legislative enhancement to better shield consumers against the hazards of defective products.